TRANSFORMASI EKONOMI DI INDONESIA PADA MASA PENDUDUKAN JEPANG 1942–1945 - Andra Pramudya Putra Andra; Ivon Octaviorin Choirunnisa Ivon; M. Aries Anirrafiqin Aries (Universitas Negeri Semarang, 2025)
The Japanese occupation from 1942 to 1945 brought drastic changes to Indonesia's economic structure, replacing the Dutch colonial orientation with a war economy system that was entirely focused on military needs. This study examines the economic conditions prior to the occupation, the core policies implemented by Japan, the dynamics of the emerging crisis, the multidimensional impact on society, and the long-term legacy for Indonesia's economic foundations after independence. Using qualitative methods based on literature review and historical sources, the study found that economic transformation during this period took place through the takeover of vital assets, the implementation of autarky, the mobilization of romusha, the compulsory surrender of crop yields, and the conversion of land for strategic industrial crops such as cotton, jute, and sisal. These policies triggered distribution disruptions, a decline in food production, hyperinflation, and mass starvation in 1944–1945. The impact was widespread in socioeconomic aspects, including the collapse of local industries, extreme poverty, and the destruction of infrastructure. The long-term legacy included the loss of capital assets, weakened production capacity, and a shift in the economic mentality of the community towards independence and local solidarity. The findings show that the Japanese occupation, although brief, had a significant structural influence on the direction of Indonesia's economy at the beginning of independence.